Correlação entre incidentes não infecciosos e tempo de internação em terapia intensiva - Thais Oliveira Gomes (2017)
The occurrence of adverse event is common in the intensive care patients and contributes to an increase in the lenght of stay, use of unit resources and mortality. However, there are few studies about the occurrence of Non Infectious Incidents (NII) especially about it´s relationship with lenght of stay. The aim of this study is to determine the correlation between the occurrence of Non Infectious Incidents (NII) and Intensive Care Unit (ICU) length of stay. We conducted an observacional prospective study done through direct observation and monitoring of NII occurrence on the ICU between july and october 2015. The sample was composed by 60 patients of what 26 (43,3%) on the group with NII and34 (56,7%) on the group without NII. Both groups were similar on the gender (p = 0,821), age (p = 0,413), severity according to SAPS III (p = 0,081), organ disfunction predicted by SOFA (p = 0,787), number of infectious disease (p = 0,241) ad time of mechanical ventilation (p = 0,335). The most frequente NII was related to lines (drains and catheters)(69,5%). The median of the dependent variable lenght of stay was twice higher in the group with NII (11; 6,75-19,5) when compared to the group without NII (5,5; 4-15,5) (p = 0,035). The correlation between the occurrence of NII and ICU lenght of stay is positive (p = 0,042) and weak (r² = 0,263). There was a positive linear trend between the increasein the lenght of stay and the occurrence of NII (p = 0,045). We conclude that the occurrence of NII is associated with a significant increase in the ICU lenght of stay. An adequate control of NII may contribute to a major turnover of ICU beds and increase their offer to patients eligible for hospitalization in the intensive care